Best Practices Pengelolaan Aset Desa Di Desa Jagalan Kabupaten Bantul - Sucahyo Heriningsih; Rusherlistyani Rusherlistyani; Dwi Sudaryati (Jurnal Ekonomi Dan Bisnis, 2017)
Assets are one of the village's potentials, which can supplement village income. Asset management must be professionally and optimally. Professionalism in asset management requires the participation of competent human resources, to realize accountable and transparent village financial reports by prioritizing good governance, it is expected that villages can increase community / stakeholder trust in village financial management. Village asset management should not be merely administrative, but more modern in handling village assets to improve efficiency, effectiveness and create added value in managing assets. The series of village asset management starts from planning needs and budgeting, Procurement, use, utilization, Security and maintenance, Deletion, Alienation, Administration, reporting, Assessment, Coaching, supervision, and control. This research uses descriptive method with case approach. The results of this study can be concluded: a) by applying economic principles, efficiency and effectiveness of potential assets of the village have been identified, and utilized optimally, so that the village assets have added value, b) a series of village assets management Jagalan has been implemented in accordance with Permendagri No.1 year 2016 on "Village Asset Management", c) supervision and control system in village asset management conducted by village head by involving BPD, d) constraint factor of asset management of village that is in asset valuation process so that it can be concluded almost no significant constraint, e) The outline of village asset management reports in Jagalan village has been reported in an accountable and transparent manner. Keywors: Village assets, accountability, transparency